2020
DOI: 10.2903/j.efsa.2020.6146
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of turmeric extract, turmeric oil, turmeric oleoresin and turmeric tincture from Curcuma longa L. rhizome when used as sensory additives in feed for all animal species

Abstract: Following a request from the European Commission, the EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of turmeric extract, turmeric oil, turmeric oleoresin and turmeric tincture from Curcuma longa L. rhizome when used as sensory additives in feed and in water for drinking for all animal species. The FEEDAP Panel concludes that the additives under consideration are safe at the maximum proposed use levels: (i) tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 92 publications
(136 reference statements)
0
12
0
Order By: Relevance
“…Pale yellow colour turmeric oil yielded values of 0.942 (25 º C), 1.5131, and +0.30 o for specific gravity, refractive index, and optical rotation, respectively. Moreover, reddish-brown colour oil was observed to demonstrate 0.981 (25 º C), 1.5288, and +2.17 o values for specific gravity, refractive index, and optical rotation, respectively (34). It is noteworthy that changing the chemical profile of the turmeric EO is the most prominent reason behind changing physicochemical properties due to slight changes in colour from pale yellow to reddish brown.…”
Section: Chemical Structure and Propertiesmentioning
confidence: 91%
“…Pale yellow colour turmeric oil yielded values of 0.942 (25 º C), 1.5131, and +0.30 o for specific gravity, refractive index, and optical rotation, respectively. Moreover, reddish-brown colour oil was observed to demonstrate 0.981 (25 º C), 1.5288, and +2.17 o values for specific gravity, refractive index, and optical rotation, respectively (34). It is noteworthy that changing the chemical profile of the turmeric EO is the most prominent reason behind changing physicochemical properties due to slight changes in colour from pale yellow to reddish brown.…”
Section: Chemical Structure and Propertiesmentioning
confidence: 91%
“…CUR content has been reported to vary from one batch of turmeric powder to another. It is widely accepted that turmeric rhizome powders contain 3–5% curcuminoids, and most turmeric extract contains about 95% curcuminoids. ,, Therefore, claimed contents for equivalent curcuminoids per serving size in the turmeric DSs were calculated based on the ratio above, except where the manufacturer labels specified otherwise. To make the data comparable, the serving size of reference rhizome powder was assumed to be 7000 mg, which is a common serving size based on the label facts of other market products (i.e., RF-1 and RF-2).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the above results, serious labeling inaccuracies were detected for the turmeric DSs. It is reported that turmeric DS products provide health benefits due to antioxidant and antiinflammatory properties. , Therefore, labeling accuracy is important for consumers to use the products safely for their intended purposes. The labeling inconsistency of turmeric DSs is also confirmed by other laboratories using different products and approaches.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From these generic case studies, the EFSA Panel on Feed and Contaminants (FEEDAP Panel) applied the approach to a number of risk assessments of multiple substances in essential oils and other preparations (e.g., extracts, oleoresins and tinctures) for use in animal species, including oregano oil [ 79 , 81 ], cardamom oil from Elettaria cardamomum (L.) Maton [ 82 ], ginger preparations [ 83 ], turmeric preparations [ 84 ], expressed lemon oil and its fractions from Citrus limon (L.) Osbeck and of lime oil from Citrus aurantiifolia (Christm.) Swingle [ 85 ], petitgrain bigarade oil from the leaves of Citrus × aurantium L. [ 86 ], expressed mandarin oil from the fruit peels of C. reticulata Blanco [ 87 ], expressed sweet orange peel oil and its fractions from Citrus sinensis (L.) Osbeck [ 88 ], bitter orange extract from the whole fruit of Citrus × aurantium L. [ 89 ], lemon extract from Citrus limon (L.) Osbeck [ 90 ], litsea berry oil from the fruits of Litsea cubeba (Lour.)…”
Section: Applications In the Human Health And Animal Health Areasmentioning
confidence: 99%